Productivity Of The Rice-Wheat Cropping System As Influenced By Nutrient Management Under Conservation And Conventional Agriculture Practices (Agronomy Journal of Nepal, 2021)
A field experiment was conducted to evaluate the productivity of rice (Oryza sativa L.) and wheat (Triticum aestivum L.) through nitrogen management practices under conservation and conventional agriculture practices during 2012-2013 at Chitwan, Nepal. The experiment on rice was conducted in strip[1]split plot design with two establishment methods (conservation agriculture and conventional practices), two rice varieties (improved variety Sabitri and hybrid Gorakhnath 509), and four nitrogen levels (0, 60, 120, and 180 kg/ha). The experiment on wheat was conducted in a split-plot design with two establishment methods and four nitrogen levels as in rice with Gautam variety. The research result revealed that the grain yield of the rice-wheat system was higher in conservation agriculture (6.6 t/ha). Gorakhnath 509 of rice followed by Gautam variety of wheat had a higher system grain yield (6.8 t/ha) than Sabitri followed by Gautam (6.5 t/ha). The highest system grain yield was obtained from 180 N kg/ha (8.1 t/ha) which was significantly higher than 0 and 60 N kg/ha but was statistically similar to 120 N kg/ha. Thus, in Chitwan and similar niches, the rice-wheat system either Sabitri followed by Gautam or Gorakhnath 509 followed by Gautam variety under conservation agriculture practices by applying 120 N kg/ha can be successfully grown by the farmers.